Antibacterial Effect of Fixed and Volatile Oils against Gram-positive and Gram-negative Bacteria - Faiq M. Salih, Tara; Ahmed Abdullah, Sakar; Ibrahim Ali, Salar; Kamal Khder, Daryan (Kurdistan Journal of Applied Research, 2019)
Antibiotic resistance phenomena among pathogenic bacteria considered as a major health problem ?and associated with increased mortality or long-term hospitalization, which lead to open a new era by using ?plant and herbal extracts as an alternative source of various chemotherapeutic drugs, also to increase antibiotic efficiency by combining with plant extract for obtaining a powerful and broad ?spectrum action. The current investigation aims to investigate antibacterial actions of fixed oils of (Olea europaea L., ?Ricinus communis L. and Linum usitatissimum) and volatile oil of (Nigella sativa, Curcuma longa L and ?Zingiber officinale) against both Staphylococcus aureus strain (6734151) and Escherichia coli ?strain (5344572). This study conducted on antibacterial effect of six ?different extracted oils from medical herbs. The findings revealed that the oil extracts have different ?antibacterial activities with efficacy. Bacterial inhibition zone was ?detected by using ?disk diffusion method. Furthermore, volatile oil of N. sativa ?showed a great inhibitory action ?against ?resistant S. aureus, which was (27.7± 1.2 mm). ?The antimicrobial effects of other fixed and volatile oils ?against S. aureu, the inhibition zone was (10 ± 1.0 mm) for (Zingiber officinale), ? (9 ± 1.0 mm) for Ricinus communis L., (7.7 ???± 0.6 mm) for Olea europea L., (7.3 ± 0.6 mm) for Linum usitatissimum and for Curcuma ?longa L. was (6.7 ± 0.6mm). Moreover, antimicrobial effect of N. sativa against ? E. coli was more ??active in comparison with other oils, while other oils showed a slight antibacterial effect?. In conclusion, volatile oil of N. sativa reveals great antibacterial activities in comparison with other extracted oils.